A new species of the feather star Capillaster within C. multiradiatus species complex (Crinoidea, Comatulidae) in Palau and the Great Barrier Reef - Meyer, David L.; Hoggett, Anne; Huang, Danwei; Rouse, Greg W.; Vail, Lyle; Yen, Ying-Hsuan; Messing, Charles G. (Zootaxa, 2025)
The feather star Capillaster AH Clark, 1909 (Crinoidea, Comatulidae) is a common feather star on coral reefs of the entire Indo-West Pacific region ranging from the Red Sea in the west to reefs of the central Pacific. Extensive studies of crinoids from the 1970s to 2000s by SCUBA diving encountered Capillaster, identified as C. multiradiatus (L., 1758) on reefs in the Palau Islands, Micronesia, and around Lizard Island (northern Great Barrier Reef [GBR], central GBR reefs (Rib Reef, John Brewer Reef, Davies Reef), reefs at Heron Island (southern GBR), and other sites within the Coral Triangle of the Ind-West Pacific. At Lizard Island and some other GBR reefs, two morphotypes co-occur in close proximity, both identified as C. multiradiatus using existing taxonomic keys, one collected by SCUBA during daytime dives when the crinoids were fully exposed and forming feeding postures and the other emergent and forming a filtration fan only at night on the same reefs where the other form occurred. The Palau form was collected exclusively when emergent at night and forming a feeding fan. Molecular genetic analysis using cytochrome oxidase c subunit I (COI) shows that the Palau crinoids cluster with the nocturnally emergent Capillaster at GBR. Diurnally emergent Capillaster at GBR sites are distinct in COI analysis from sympatric nocturnally emergent specimens and also in newly recognized skeletal morphologic characters and distinct color variation. We utilize molecular genetic data, traditional skeletal morphology, coloration, along with differences in emergence and feeding habits to describe a new species, Capillaster crypticus sp. nov.,which is currently known from Palau reefs and GBR reefs. A single specimen collected in daytime at Raja Ampat, Indonesia, clustered with C. crypticus on COI yet we could not confirm whether it lacks the indentation in the center of the centrodorsal. This new species represents another example of “hidden diversity” among the species-rich feather star crinoid faunas of the Indo-West Pacific region. Our data emphasize the importance of utilizing all available data: genetic, skeletal morphologic, color and pattern, ecologic, behavioral, and reproductive in distinction of crinoid species.